Respuesta:
a) 59
b) -35
Explicación paso a paso:
a) 12 + 3 − 15 ÷ (- 2 -1) + 30 – 64 ÷ 8 − 2 + 10 - 72 ÷ (− 8) =
12+3-15÷(-3)+30-8-2+10-(-9)
12+3-(-5)+30-8-2+10+9
12+3+5+30-8-2+10+9=59
b) [(- 6 +8) − (- 15) ÷ 3] x {- 8 – [- 2 + (8 + 2) ÷ (- 3 – 2)] + (- 4 + 8 – 5)} =
[2-(-5)]×{-8-[-2+10÷(-5)]+(-1)}
7×{-8-[-2+(-2)]-1}
7×{-8-[-2-2]-1}
7×{-8-(-4)-1}
7×(-5)=-35
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
Respuesta:
a) 59
b) -35
Explicación paso a paso:
a) 12 + 3 − 15 ÷ (- 2 -1) + 30 – 64 ÷ 8 − 2 + 10 - 72 ÷ (− 8) =
12+3-15÷(-3)+30-8-2+10-(-9)
12+3-(-5)+30-8-2+10+9
12+3+5+30-8-2+10+9=59
b) [(- 6 +8) − (- 15) ÷ 3] x {- 8 – [- 2 + (8 + 2) ÷ (- 3 – 2)] + (- 4 + 8 – 5)} =
[2-(-5)]×{-8-[-2+10÷(-5)]+(-1)}
7×{-8-[-2+(-2)]-1}
7×{-8-[-2-2]-1}
7×{-8-(-4)-1}
7×(-5)=-35